Planning and design office interior / Aisah Lamsah - Lamsah, Aisah (Faculty of Architecture, Planning and Surveying, 1982)
In the past, books about the planning and design of offices generally fell into two categories. One described the practical problems of "how to," The second presented office design in beautiful photographs of handsome installations. Up until now, there has been very little discussion of the critical issues that underlie planning and design decisions. Such a lack of self-examination may be attributed to the rapid growth of the field. Recently, designers and management have begun to examine the elements that comprise the work environment. What is emerging is a new and unique realization - that the space planner, whether architect or interior designer, is part of a management consulting team. This book is concerned with examining the basic problems of design and planning with regard to the growing body of knowledge of how people work and the changing technologies of the office. It is an expanding subject with contributions from a host of consultants in the social sciences, hardware, acoustics, computers, lighting, paper flow, and audiovisual fields. The aesthetic, functional, and psychological aspects of the office have become very specialized subjects in a relatively short period of time. Because it is a serious subject for examination and study, the office offers a creative challenge to designers and architects. The problem of putting people and furniture in space does not exist in a vacuum. Pragmatically, the furniture and space in our buildings are not ideal. Buildings constructed for tenants may work well for small firms, such as lawyers and insurance companies, but may beunsuited for large . users of space who might be a single tenant of a floor or more. The architect cannot be a hero to both kinds of users. If management decides to build its own facility, can designers suggest the ideal space for that purpose? Designers are still learning about space. They are learning about how large and unlimited a space can be before we feel it is too large. We still cannot say what the most comfortable and "efficient size of space would be to work in, 8,000, 20,000, or 40,000 square feet.